Development of a Field Simulation-Based MISP for Reproductive Health Module for Undergraduate Midwifery Students at STIKES RSPAD Gatot Soebroto - Manggiasih Dwiayu Larasati; Dina Raidanti (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
The Minimum Initial Service Package (MISP) for Reproductive Health is a critical disaster intervention requiring robust cognitive and psychomotor readiness from midwifery students. However, traditional education often fails to replicate chaotic, real-world disaster dynamics. To bridge this gap, this study developed and evaluated a field simulation-based MISP Reproductive Health module designed to enhance undergraduate midwifery students' knowledge and skills. Using a Research and Development (R&D) approach guided by the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework, the implementation phase utilized a quasi-experimental pre-post test control group design. Sixty final-year midwifery students were divided equally into an intervention group (new module with field simulations) and a control group (conventional module with traditional lectures). Data were gathered via knowledge questionnaires and simulation-based OSCE checklists, then analyzed using Paired and Independent T-Tests. The development phase demonstrated high feasibility, with material and media experts validating the module at 92% and 88%, respectively. Post-implementation, the intervention group showed significant increases in mean scores for both knowledge (p < 0.001) and skills (p < 0.001). Furthermore, comparative analysis revealed that the intervention group achieved substantially higher scores in team coordination and tactical field execution than the control group. In conclusion, this field simulation-based MISP Reproductive Health module is valid, effective, and highly feasible for improving essential disaster preparedness competencies in future midwifery professionals.